DECREASE LEVELS OF IRON (Fe) AND MANGANESE (Mn) IN ACID MINING WATER USING ACTIVE CARBON OF EGG SHELL - Sandri Tandi Rapang; Shalaho Dina Devy; Windhu Nugroho; Harjuni Hasan; Revia Oktaviani; Tommy Trides (Universitas Mulawarman, 2022)
Acid mine drainage is acidic water that arises as a result of mining activities. Acidic water has a high acidity, which is often characterized by a low pH and contains high levels of heavy metals Fe and Mn. The purpose of this study was to determine the effect of activated carbon on the adsorption process and the effect of mass of activated carbon on eggshells. The method used in this research is the adsorption method using activated carbon of eggshell which is physically and chemically activated. This study used a mass variation of 5, 10, 15 and 20 grams with a contact time of 30 minutes and an adsorbent size of 200 mesh. The parameters studied were heavy metals iron (Fe) and manganese (Mn). The initial concentration of Fe acid mine waste was 29.179 mg/L, and Mn was 7.9692 mg/L. The results showed that the mass of activated carbon had an effect on decreasing the levels of Fe and Mn metals. On physical activation the average decrease in Fe metal was 99.50% and Mn metal was 53.21%, while on chemical activation the average decrease in Fe metal was 97.72% and Mn metal was 97.97%.Keywords: Acid mine water, Fe, Mn, Activated carbon, egg shell